Impact of long-term high-intensity interval and moderate-intensity continuous training on subclinical inflammation in overweight/obese adults - Gerosa-Neto, José (J Exerc Rehabil, 2016)
Obesity is a risk factor able to trigger several inflammatory alterations and the imbalance between pro- and anti-inflammatory cytokine productions. Physical exercise is an important strategy for reduction of inflammatory established process. The aim of this study was to evaluate the effect of 16 weeks of three exercise training programs in the inflammatory profile and insulin resistance in overweight/obesity. Thirty two men and women (46.4±10.1 years; 162.0±9.1 cm; 82.0±13.6 kg) were divided into three groups for training on a treadmill: continuous at 70% maximum heart rate (HRmax) 5 times a week (CONT); 1×4 min (1-bout) and 4×4 min (high intensity interval training, HIIT) at 90% HRmax 3 times a week. Interleukin (IL) 6 and IL-10, tumor necrosis factor-alpha (TNF-α), insulin and adiponectin levels were analyzed by enzyme-linked immunosorbent assay, and homeostasis model assessment insulin resistance was calculated. After 16 weeks of training blood concentrations of IL-6 decreased in the HIIT group (P=0.035), TNF-α decreased in the CONT (P=0.037) and increased in HIIT (P=0.001) and adiponectin decreased in the three training models. There was a trend towards decreased body weight and body mass index (BMI) after HIIT only (P=0.059 and P=0.060, respectively). Despite the decrease of adiponectin and the increase of TNF-α in HIIT group, insulin sensitivity showed a trend for improvement (P=0.08). HIIT program decreased IL-6 at rest and although not significant was the only who tended to decrease total body weight and BMI. Taken together, our data suggest that both HIIT as well as CONT exercises training program promotes changes in inflammatory profile in overweight/obesity, but dissimilar response is seen in TNF-α levels.